Global Trends of STEAM Research in Science Education (2010–2025): A Bibliometric Review - Dedi Prasojo; Syamsu Syamsu; Sudarsono Sudarsono; Supriyatman Supriyatman; Afadil Afadil; Rafiqa Rafiqa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Science education has experienced a substantial paradigm shift over the last decade, driven by the demands of the twenty-first century, rapid technological advancement, and the need for innovative, multidisciplinary approaches to learning. This study aims to examine global research trends in STEAM (Science, Technology, Engineering, Arts, and Mathematics) within the context of science education from 2010 to 2025 using a bibliometric approach. Data were retrieved from the Scopus database and analyzed using Biblioshiny, VOSviewer, and Microsoft Excel to map publication growth, citation patterns, collaboration networks, and thematic development. A total of 114 Scopus-indexed journal articles were identified and analyzed following a rigorous screening process based on predefined inclusion and exclusion criteria. The results indicate a substantial increase in STEAM-related publications, particularly after 2018, reflecting growing global interest in interdisciplinary and creativity-oriented science education. The United States emerged as the most productive and influential country, with strong international collaboration networks. Keyword and thematic analyses reveal that “science education,” “STEAM,” and “engineering education” function as motor themes, while “STEM,” “curriculum,” and “creativity” serve as foundational themes. Emerging topics such as computational thinking and computer science education highlight the increasing integration of digital competencies in STEAM pedagogy. Overall, the findings demonstrate that STEAM research in science education has evolved into a dynamic and interdisciplinary field, providing valuable insights for researchers, educators, and policymakers in shaping future research directions and educational practices.